2016
DOI: 10.5815/ijmecs.2016.05.02
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble of Adaptive Neuro-Fuzzy Kohonen Networks for Online Data Stream Fuzzy Clustering

Abstract: Abstract-A new approach to data stream clustering with the help of an ensemble of adaptive neuro-fuzzy systems is proposed. The proposed ensemble is formed with adaptive neuro-fuzzy self-organizing Kohonen maps in a parallel processing mode. Their learning procedure is carried out with different parameters that define a nature of cluster borders' blurriness. Clusters' quality is estimated in an online mode with the help of a modified partition coefficient which is calculated in a recurrent form. A final result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Hu et al proposed a new method for data stream clustering with the help of adaptive neuro-fuzzy system integration. He found that the proposed ensemble is formed by adaptive neuro-fuzzy self-organizing feature maps in the parallel processing mode, and the final result is selected by the best neuro-fuzzy self-organizing feature maps [6]. Denial of service is also one of the most pressing security threats to in-vehicle network systems.…”
Section: Related Workmentioning
confidence: 99%
“…Hu et al proposed a new method for data stream clustering with the help of adaptive neuro-fuzzy system integration. He found that the proposed ensemble is formed by adaptive neuro-fuzzy self-organizing feature maps in the parallel processing mode, and the final result is selected by the best neuro-fuzzy self-organizing feature maps [6]. Denial of service is also one of the most pressing security threats to in-vehicle network systems.…”
Section: Related Workmentioning
confidence: 99%
“…Terdapat beberapa penelitian terdahulu yang membahas mengenai pemanfaatan jaringan Kohonen. Penelitian [4] dan [5] memanfaatkan jaringan Kohonen neuro-fuzzy untuk klusterisasi stream data. Jaringan Kohonen dan Support Vector Machine dapat juga digunakan untuk pendeteksian intrusi [6].…”
Section: Pendahuluanunclassified